Governança nas organizações da sociedade civil de interesse público - Paulino, Cleane Ramos (2020)
Governance provides to direct, monitor and encourage organizations to achieve organizational objectives in a sustainable way. Thus, for this to be possible, it is necessary to adopt Governance practices, based on principles and pillars that direct these practices to be adopted by all organizations. This study analyzed the Governance practices adopted by Civil Society Organizations of Public Interest (OSCIP), based on the principles and pillars recommended by IBGC, recommended in the Guide of Best Practices for Third Sector Organizations: Associations and Foundations. The research is characterized as exploratory and descriptive, with a predominantly quantitative data approach, carried out through bibliographic and survey research, for access to primary data with survey application. A census was applied among the 46 OSCIP of the Municipality of Fortaleza (CE), able to participate in the research, obtaining 20 answers. Based on the analysis of the data, itis that the OSCIP of Fortaleza (EC), adherin to the Governance practices recommended by IBGC (2016), in accordance with the Principles of: Transparency; Equity; Accountability; and Corporate Responsibility, as well as the Pillars: Mission, brand name and respect for laws; Forms of constitution and higher organs; Superior collegiate body: Board of Directors or Board of Trustees; Organizational Management or Executive Board; Independent Audit; Fiscal Council; Conduct, Conflict of Interest and Disclosure of Information. The mean adherence of the practices was 88.4% and a median equal to five, a maximum score, and the statistically significant difference was not verified, at the confidence level of 95%, evidencing the high level of adoption of governance practices by the entities surveyed.